Management and entrepreneurship - Havinal, Veerabhadrappa (New Delhi : New Age International, 2009)
About the Book: Of late, academicians of technical education have felt the importance of ''Management'' and ''Entrepreneurship''. Engineers need to manage their departments/sections/subordinates, and Entrepreneurship helps the large pool of technical manpower in developing small-scale industries in high tech areas thereby contributing to the economy of the country. This book covers both 'Management' and 'Entrepreneurship'. The first chapters of this book deal with Management, Planning, Organizing and Staffing, Directing and Controlling. The last four chapters deal with Entrepreneurship, Small-Scale Industries, Institutional support and Project formulation. Adequate number of simple examples with which the students are familiar are included in each chapter. In addition, each chapter contains student learning activities to give the readers a chance to enhance the learning process. Though the book is written keeping in mind the syllabus of Visvesvaraya Technological University, yet it is useful for B.Com, BBM, DBM, . PGDBM and MBA students also. Contents: Management Planning Organizing and Staffing Directing and Controlling Entrepreneurship Small-Scale Industries Institutional Support Preparation of Project.
Chapter 1. Management -- 1.1 Meaning -- 1.2 Characteristics of Management -- 1.3 Nature of Management -- 1.4 Management Functions or the Process of Management -- 1.5 Functional Areas of Management -- 1.6 Management: A Science or ART? -- 1.7 Management: A Profession? -- 1.8 Management and Administration -- 1.9 Role of Management -- 1.10 Levels of Management -- 1.11 Evolution of Management -- Chapter Summary -- Questions -- Chapter 2. Planning -- 2.1 Meaning -- 2.2 Nature of Planning -- 2.3 Importance of Planning -- 2.4 Types of Planning -- 2.5 Types of Plans -- 2.6 Steps in Planning -- 2.7 Decision-Making -- Chapter Summary -- Questions -- Chapter 3. Organizing and Staffing -- 3.1 Meaning and Definitions of Organizing -- 3.2 Steps in Organizing -- 3.3 Nature of Organization -- 3.4 Organization Structure -- 3.5 Purpose of Organization -- 3.6 Principles of Organization -- 3.7 Departmentation -- 3.8 Types of Organization -- 3.9 Span of Control -- 3.10 Authority, Power and Responsibility -- 3.11 Delegation of Authority -- 3.12 Centralization and Decentralization -- 3.13 Delegation vs Decentralization -- 3.14 Management by Objectives [MBO] -- 3.15 Meaning of Staffing -- 3.16 Nature and Importance of Staffing -- 3.17 Recruitment -- 3.18 Selection -- Chapter Summary -- Questions -- Chapter 4. Directing and Controlling -- 4.1 Meaning and Nature of Direction -- 4.2 Principles of Directing -- 4.3 Leadership and Leadership Styles -- 4.4 Motivation -- 4.5 Communication -- 4.6 Noise and Feedback in Communication -- 4.7 Importance of Communication -- 4.8 Channels of Communication -- 4.9 Types of Communication -- 4.10 Forms of Communication -- 4.11 Coordination -- 4.12 Coordination and Cooperation -- 4.13 Importance of Coordination -- 4.14 Techniques of Coordination -- 4.15 Managerial Control -- 4.16 Steps in a Control Process -- 4.17 Essentials of a Sound Control System -- 4.18 Control Methods -- Chapter Summary -- Questions -- Chapter 5. Entrepreneurship -- 5.1 Evolution of Concept of Entrepreneur -- 5.2 Concept of Entrepreneur -- 5.3 Characteristics of Entrepreneur -- 5.4 Distinction Between Entrepreneur and Manager -- 5.5 Technical Entrepreneur -- 5.6 Charms of Being An Entrepreneur -- 5.7 Functions of an Entrepreneur -- 5.8 Types of Entrepreneur -- 5.9 Intrapreneurs -- 5.10 Ultrapreneurs -- 5.11 Concept of Entrepreneurship -- 5.12 Evolution of Entrepreneurship -- 5.13 Role of Entrepreneurship in Economic Development -- 5.14 Stages in the Entrepreneurial Process -- 5.15 Barriers to Entrepreneurship -- Chapter Summary -- Questions -- Chapter 6. Small Scale Industry -- 6.1 Meaning and Definition of Small Scale Industry -- 6.2 Characteristics of SSI -- 6.3 Rationale -- 6.4 Objectives -- 6.5 Scope -- 6.6 Role of SSI in Economic Development -- 6.7 Advantages of Small Scale Industries -- 6.8 Steps to Start an SSI -- 6.9 Government Policy: Industrial Policy Resolutions -- 6.10 Government Support to SSI during Five Year Plan -- 6.11 Impact of Globalization and Liberalization on SSI -- 6.12 Impact of WTO/GATT on SSI -- 6.13 Support -- 6.14 Agencies of Government for SSI -- 6.15 Nature and Types of Support -- 6.16 Ancillary, Tiny and Service Industries -- Chapter Summary -- Questions -- Chapter 7. Institutional support -- Chapter 8. Preparation of project.
Includes bibliographical references (page 177) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Management -- India -- Textbooks; Entrepreneurship -- India -- Textbooks; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; Entrepreneurship; Management; India; Textbooks; Textbooks